(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Describe the clinical and paraclinical characteristics and evaluate the results of fungal etiology identification in patients with fungal pneumonia treated at Hanoi Medical University Hospital. Methods: Conduct a cross-sectional descriptive study on 153 eligible patients with a diagnosis of fungal pneumonia and fungal etiology identification results who were treated as inpatients at Hanoi Medical University Hospital from January 2023 to January 2025. Results: The average age was 65.75 ± 13.00, the age range from 60-75 accounted for 48.4%, male/female was 3/1. The main clinical symptoms included cough with phlegm (68%), shortness of breath (67.3%), fever (62.7%), decreased lung ventilation (68.6%), crackles (66%), and respiratory failure (65.4%). Common underlying diseases include diabetes (35.3%), COPD (33.3%), heart failure (16.3%), solid tumor (15%), and other chronic respiratory diseases (12.4%). Lung lesions on chest CT scans are mainly seen on both sides (86.3%), with consolidation (69.9%), bronchial wall thickening (64.4%), and ground glass (62.3%). Most patients have increased CRP (92.4%), increased PCT (98.4%), and increased neutrophil (80,4%). The most commonly isolated fungal pathogens are Candida spp. (80,4%) and Aspergillus spp. (18,3%). Conclusion: The clinical and paraclinical characteristics of patients with fungal pneumonia are diverse. Diagnosis must combine both symptoms, risk factors in the patient and fungal test results to assess and predict treatment.